Demineral Drinking Water As A Bladder Irrigation During TURP (Transurethral Resection Of The Prostate) On Serum Electrolyte Levels: Penggunaan Air Minum Demineral Sebagai Cairan Irigasi Buli Pada Tindakan TURP (Transurethral Resection Of Prostate) Terhadap Kadar Serum Elektrolit - Bekti Setiawan; Hidayah, Nurul; Fakhri Surahmad (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: TURP procedure is recommended to treat symptoms of Benign Prostatic Hyperplasia (BPH) indicated for surgery. Irrigation method is the main factor in the success and evaluation of TURP syndrome. There is no ideal irrigation fluid or consensus result of the best irrigation fluid for TURP. Several irrigation materials have been developed related to effectiveness and cost considerations. Demineralized drinking water is an alternative for bladder irrigation of patients with TURP. The purpose of this study was to analyze the use of demineralized drinking water on serum electrolyte levels in patients before and after TURP. Methods: Using the pre-experiment method with a pre-post-test one group design approach, samples were selected using a purposive sampling technique of 15 respondents, analysis using the Wilcoxon signed ranks test. Results: The results of the univariate analysis showed that almost all respondents received an irrigation volume of 20 liters (93.3%), most respondents were irrigated for 60 minutes (73.3%). The sig.(2-tailed) value of serum Sodium 1.00 > 0.05, Potassium 0.655 > 0.05, and Chloride 0.655 > 0.05, showed no significant difference in the average results of serum electrolyte examination between pre and post-test. Conclusions: There is no effect of using demineralized drinking water as a bladder irrigation fluid in TURP procedures on serum electrolyte levels in BPH patients. The results of this study provide a strong basis for considering the use of demineralized drinking water as an option in clinical practice for bladder irrigation in TURP procedures.